PENGARUH LEVERAGE, FIRM SIZE, DAN TIMELINESS TERHADAP EARNINGS RESPONSE COEFFICIENT - Hartanto, Bianca Natalie; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to obtain empirical evidence regarding the effect of leverage, firm size, and timeliness on the earnings response coefficient. This study used basic materials sector companies that were registered on the Indonesia Stock Exchange during 2018-2021, the sample was selected using the purposive sampling method and there were 43 companies that met the criteria. The data obtained was then processed using Microsoft Excel 365 and Eviews 12 software. The results in this study stated that leverage and timeliness have no significant effect on the earnings response coefficient. Meanwhile, firm size has a positive and significant effect on the earnings response coefficient. The implication of this study is firm size influences investors in investing decisions.